Investigation of chemical differentiation among the NGC 2264 cluster-forming clumps. Issue 2 (10th January 2020) - Taniguchi, Kotomi; Plunkett, Adele; Herbst, Eric; Dobashi, Kazuhito; Shimoikura, Tomomi; Nakamura, Fumitaka; Saito, Masao
ABSTRACT: We have carried out mapping observations of molecular emission lines of HC3 N and CH3 OH toward two massive cluster-forming clumps, NGC 2264-C and NGC 2264-D, using the Nobeyama 45-m radio telescope. We derive an I (HC3 N)/ I (CH3 OH) integrated intensity ratio map, showing a higher value at clumps including 2MASS (Two Micron All Sky Survey) point sources at the northern part of NGC 2264-D. Possible interpretations of the I (HC3 N)/ I (CH3 OH) ratio are discussed. We have also observed molecular emission lines from CCS and N2 H + toward five positions in each clump. We investigate the N (N2 H + )/ N (CCS) and N (N2 H + )/ N (HC3 N) column density ratios among the ten positions in order to test whether they can be used as chemical evolutionary indicators in these clumps. The N (N2 H + )/ N (CCS) ratio shows a very high value toward a bright embedded IR source (IRS1), whereas the N (N2 H + )/ N (HC3 N) ratio at IRS1 is comparable with those at the other positions. These results suggest that ultraviolet radiation affects the chemistry around IRS1. We find that there are positive correlations between these column density ratios and the excitation temperatures of N2 H +, which implies the chemical evolution of clumps. These chemical evolutionary indicators likely reflect the combination of evolution along the filamentary structure and evolution of each clump.